Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf02067335
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic tumors in multiple endocrine neoplasia type 1: Clinical presentation and surgical treatment

Abstract: Among 33 patients with endocrine pancreatic tumors due to multiple endocrine neoplasia type 1 (MEN-1), 19 (58%) patients had hypergastrinemia, 7 (21%) patients had hyperinsulinism, and 7 (21%) patients had clinically non-functioning lesions. At least one gross tumor was found in all patients undergoing pancreatic surgery, including those with negative localization studies prior to operation. The patients also had additional macroscopic tumors as well as numerous microadenomas, and the lesions frequently were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 22 publications
0
101
0
5
Order By: Relevance
“…In smaller series from the last decade, distant metastases are reported in 6-22% (Bartsch et al 2005, Davi et al 2011, Lopez et al 2011, whereas in a report from 1992 distant metastases were observed in 57% (Grama et al 1992). Mean tumor size in this latter series was 6.7 cm (Grama et al 1992).…”
Section: Epidemiologymentioning
confidence: 53%
See 1 more Smart Citation
“…In smaller series from the last decade, distant metastases are reported in 6-22% (Bartsch et al 2005, Davi et al 2011, Lopez et al 2011, whereas in a report from 1992 distant metastases were observed in 57% (Grama et al 1992). Mean tumor size in this latter series was 6.7 cm (Grama et al 1992).…”
Section: Epidemiologymentioning
confidence: 53%
“…Reports regarding the prognostic significance of pancreatic tumor size vary. No relation between tumor size and metastases, malignancy or overall survival is found in several series reporting on MEN1-related dpNETs (hormonally active and NF; Grama et al 1992, Lowney et al 1998, Lairmore et al 2000, Bartsch et al 2005, Kouvaraki et al 2006, Lopez et al 2011. In the subset of NF-pNETs, larger tumor size was related to a higher rate of metastases and a decreased overall survival (Triponez et al 2006a,b).…”
Section: Prognostic Factorsmentioning
confidence: 98%
“…This may in part explain the shift in relative incidence from F-PNETs to NF-PNETs in recent years. Whereas in early single-center series, NF-PNETs comprise 18%-66% of all neuroendocrine tumors of the pancreas [27][28][29][30][31][32], recent large, singlecenter or epidemiologic studies classify 68%-90% as NFPNETs [21,26,[33][34][35].…”
Section: Incidencementioning
confidence: 99%
“…3,13,14 Gastrinoma in MEN1 is the most prevalent functioning PET, seen in 30% to 75% of MEN1 cases 5 . The gastrinomas in MEN1 mostly occur in the duodenum (up to 90%) and is frequently multifocal, in contrast to unifocal sporadic gastrinomas.…”
Section: Endopancreatic Tumors In Men1mentioning
confidence: 99%